Re-examining the early history of the Leiden jar: Stabilization and variation in transforming a phenomenon into a fact. (September 2018) - Silva, Cibelle Celestino; Heering, Peter
In this paper, we examine the period that immediately followed the invention of the Leiden jar. Historians of science have developed narrations that emphasize the role of grounding during the process of charging the jar. In this respect, this episode shows significant aspects that can be used to characterize science, scientific knowledge production, and the nature of science. From our own experimentation, we learned that grounding was not necessary in order to produce the effect. These experiences inspired us to go back to primary sources. In doing so, we came to a new understanding of the early period after Kleist's and Musschenbroek's initial creation of the effect. From our analysis, we conclude that it is not the grounding which was perceived as a major innovation (as well as a challenge) during this early period of the discussion but the concept of an electrical circuit. This understanding was fundamental in characterizing the Leiden jar as a new device challenging the then current knowledge of experimental practices in the field of electricity.